Not a Benign (Mis)Label: Penicillin Allergy Education for the Nonallergist - Jessica Plager; William B. Cutrer (Association of American Medical Colleges, 2024)
Introduction Up to 20% of the US population carries a penicillin allergy label; however, over 95% of those patients can safely tolerate penicillin. This discrepancy has important personal and public health consequences. There is no published curriculum for medical trainees that covers penicillin allergy history taking, risk assessment, and antibiotic prescribing. Methods We created a 60-minute, interactive curriculum that targeted medical students during their internal medicine rotation. We employed learning strategies including didactics, case-based learning, and role-playing. We compared self-efficacy and knowledge before and after the intervention using paired t tests. Results A total of 28 medical students participated, with 25 completing both the pre- and postworkshop surveys. There was a statistically significant improvement in student-rated preparedness to prescribe antibiotics to patients with a penicillin allergy label (p < .001) and determine whether a patient has a history of an allergic reaction that was severe or life-threatening (p < .001). There was additionally a statistically significant increase in students' perception that penicillin allergy labels carry important health consequences (p = .005), as well as increase in their total knowledge scores (p = .006). Discussion The workshop employs adult learning techniques to improve self-efficacy and knowledge regarding penicillin allergy in medical students. Further work is needed to refine the curriculum, seek external validity, and determine the impact of this workshop on clinical outcomes.